2017
DOI: 10.1007/s00277-017-3073-z
|View full text |Cite
|
Sign up to set email alerts
|

A prolonged microscopic observation improves detection of underpopulated cells in peripheral blood smears

Abstract: We evaluated an extended time in the microscopic review in samples in which the potential clinical information could be increased with respect to those that could be achieved with the usual laboratory methodologies. We used samples containing nucleated red blood cells in a small amount and cytopenic samples. For these purposes for each peripheral blood smear, the timing of eye-count differential was increased up to 20 min, regardless of the final number of cells which could be counted. In addition, an automate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Other DM analyzers include Vision Pro (West Medica, Perchtoldsdorf, Austria), EasyCell assistant (Medica, Bedford, MA, USA), Nextslide (Nextslide Imaging, LLC, Cleveland, OH, USA), and so on [ 1 ]. Since DM analyzers were first developed in the 1970s, a number of studies have been reported to evaluate the performance of DM analyzers [ 1 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other DM analyzers include Vision Pro (West Medica, Perchtoldsdorf, Austria), EasyCell assistant (Medica, Bedford, MA, USA), Nextslide (Nextslide Imaging, LLC, Cleveland, OH, USA), and so on [ 1 ]. Since DM analyzers were first developed in the 1970s, a number of studies have been reported to evaluate the performance of DM analyzers [ 1 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to evaluate the performance of DM analyzers on WBC differentials by focusing on leukopenic samples. Most of previous studies evaluated DM analyzers using pathological samples including some leukopenic samples [ 1 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. To the best of our knowledge, however, there has been no study that analyzed leukopenic samples separately as the main subjects to fully evaluate the performance of DM analyzers, including precision [ 1 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the known inaccuracy of the microscopic versus instrumental cellular count should be considered, especially in underpopulated cells 18 …”
Section: Discussionmentioning
confidence: 99%
“…Even considering the known inaccuracy of manual cellular counting in the case of underpopulated cells, mostly, 18 the likelihood of IM increases progressively as the reactive lymphocytes percentage in the PB increases, even more so when the presence of these cells occurs associated with a relative lymphocytosis of more than 50% 28 . Contrary, the diagnostic value assigned to APCs concerns only the qualitative data of their presence, 11,13,14 while their quantification does not seem to have clinical‐prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Vision Hema (West Medica, Austria) is an automated system for digital scanning of stained peripheral blood smears and preclassification of leukocytes, erythrocytes, and platelets . The intervention of an observer is always necessary at the end to confirm allocation of the cells in the proper group and/or to correct allocation by moving cells to the proper group as anticipated by the real‐time digital color‐image of the single cells on the screen.…”
Section: Methodsmentioning
confidence: 99%